Introducing proactive sovereign disaster risk financing in India: Potentials and challenges. (15th February 2022) - Panwar, Vikrant; Sen, Subir; Shaw, Rajib
Abstract: This study explores the possibilities and challenges of introducing ex-ante or proactive disaster risk financing (DRF) solutions such as mitigation funds, credit arrangements, risk transfer instruments for enhancing disaster resilience at the national and sub-national levels in India. A survey using a structured questionnaire was undertaken considering a select group of respondents directly involved in the development and execution of various disaster risk reduction (DRR) and risk financing strategies. The respondents were from the government and non-government entities, identified as key stakeholders with the assumption that the views obtained reflect the disaster-related funding needs of the government and supporting organizations, respectively. The identification of a set of enabling factors is based on the aggregation and systematic analysis of responses. The study, in doing so, offers an insight on the understanding of the respondents on DRF, the existing gaps and scope in disaster prevention and management policies, their limitations and implementation challenges. The analysis generates important policy recommendations for governments at different levels in India that could foster the initiatives towards building disaster resilience. The study argues in favour of a demand for developing a mix of both ex-ante and ex-post disaster financing measures in India rather than relying only on the latter. A diversified approach may safeguard the human and economic assets, control short and long-term fiscal consequences and minimize overall developmental losses due to disasters.